2016
DOI: 10.1163/9789004317437
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Dhofari Arabic

Abstract: Declaration Copyright Acknowledgements 1 Introduction 1.1 Aim and scope of this study 1.2 Geography 1.3 History: political and socioeconomic 1.4 Linguistic diversity in Dhofār 1.5 Literature review 1.5.1 Rhodokanakis and the Süd-Arabische Expeditions of the Austrian Imperial Academy 1.5.2 Arabic dialects 1.6 Methodology 1.7 Conclusion and recommendations for further study. 2 Phonology 2.1 Consonant inventory 2.1.1 Stops 2.1.2 Fricatives 2.1.3 Nasals 2.1.4 Laterals 2.1.5 Flaps 2.1.6 Glides 2.1.7 Marginal phonem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 6 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…However, for the majority of outcomes assessed using GRADE, statistical heterogeneity was mostly low, countering claims (e.g. Davey 2016), that some of the trials had unreliable results due to being outdated or flawed. Only one outcome (length of maternal stay) was downgraded further to very low-quality evidence due to inconsistency.…”
Section: Quality Of the Evidencementioning
confidence: 91%
See 1 more Smart Citation
“…However, for the majority of outcomes assessed using GRADE, statistical heterogeneity was mostly low, countering claims (e.g. Davey 2016), that some of the trials had unreliable results due to being outdated or flawed. Only one outcome (length of maternal stay) was downgraded further to very low-quality evidence due to inconsistency.…”
Section: Quality Of the Evidencementioning
confidence: 91%
“…Both observational studies and systematic reviews of randomised controlled trials of timing of induction have shown mixed findings for outcomes such as perinatal death and caesarean section rates (Davey 2016).…”
Section: Agreements and Disagreements With Other Studies Or Reviewsmentioning
confidence: 99%
“…For the rest of the 20 th century, Omani dialects have been pretty much neglected by the scholarly community (with the important exception of Holes, 1989). It was not until the last decade that the literature about Omani Arabic started to flourish again: see, among others, Holes (2008), Eades (2009Eades ( , 2012, Eades and Persson (2013), Eades and Watson (2013) and Davey (2016). 2.…”
Section: Notesmentioning
confidence: 99%
“…The title of the article summed up the consequences of the ALEC-written and AFP-and SPN-supported legislation quite succinctly: With Fewer Members, a Diminished Political Role for Wisconsin Unions. 54 One public sector union leader in Wisconsin quoted in the article reflected on the legislation in the following way: "Do we have less boots on the ground? Yeah.…”
Section: Conservative Advocacy Weaponized Policy Feedbacks and The mentioning
confidence: 99%